Clonagem e caracterização das isoformas de luciferases de lanternas e corpo gorduroso do vagalume Aspisoma lineatum (Lampyridae: Cratomorphini): origem estrutural e evolutiva das luciferases pH-sensitivas mais eficientes à partir de ancestrais pH-insensitivas - Carvalho, Mariele Cristina de (Universidade Federal de São Carlos, 2020)
Firefly luciferases emit yellow-green light with high efficiency at physiological pH. However, under acidic conditions, in the presence of heavy metals or high temperatures, they emit red light. To understand the structural origin of the different colors of bioluminescence and the sensitivity to pH, more than 30 luciferases of fireflies have already been cloned, sequenced and characterized. Recently, the binding site for protons and metals in luciferases has been determined. However, how the efficient pH-sensitive luciferases of firefly lanterns emerged and evolved is not clear. Therefore, in this work, the cloning, characterization and comparison of the cDNAs of the isozymes of the luciferases of the lanterns and the fatty body of the firefly Aspisoma lineatum (Lampyrinae: Cratomorhini) was carried out in order to better understand the origin and evolution of the sensitivity to pH. The isoform AL2 from the fat body has 545 amino acids, extremely slow kinetics and an emission spectrum insensitive to pH variations. In contrast, the AL1 isoform found in the adult lantern has 548 amino acids, flash-type kinetics, pH-sensitive spectrum and a catalytic efficiency 10x greater than the AL2 isoform. Analysis of thermal stability and CD spectra showed that the pH-insensitive form is much more thermostable and rigid than the lanterns isoform and other firefly luciferases investigated so far. The position H310, which is involved in the pH sensitivity of firefly luciferases, is replaced by a glutamine in the lantern isoform and by glutamate in the fat body one, indicating that the substitution E310Q may be determinant for the origin of the phenotype pH-sensitive. These results indicate that the pH-sensitive luciferases, found in firefly lanterns, originated from a more rigid, pH-insensitive, less efficient ancestral luciferase. These results also show that the isoform AL2, due to its high thermostability, has potential for biotechnological applicability.
Cloning and characterization of luciferase isoforms from lanterns and fat body of the firefly Aspisoma lineatum (Lampyridae: Cratomorphini): structural and evolutionary origin of most efficient pH-sensitive luciferases from pH-insensitive ancestors
Keywords: Bioluminescência; Luciferases; Sensibilidade ao pH; Aspisoma lineatum; Bioluminescence; Luciferases; pH-sensitivity; CIENCIAS BIOLOGICAS::BIOQUIMICA